The very best of Ma Rainey [compact disc]. - Rainey, Ma, 1886-1939 (Heroes of the blues., 2003)
Rainey was known as The Mother of the Blues for good reason. Her voice filled any room with the energy and spunk expected in blues music. Features the best songs from this legendary blues singer.